THE TRANSFER PRICING FILE AND TAX CONTROVERSIES - AN EMPIRICAL STUDY - Anatol Melega; Marioara Molociniuc Hritcan; Anamaria Geanina Macovei (Studies and Scientific Researches: Economics Edition, 2022)
Transfer pricing is a real challenge for both tax regulators and multinationals who use this procedure, in most cases to erode the tax base. The purpose of this paper is to analyse the tax practices and regulations of countries applying OECD transfer pricing regulations. To this end, the profiles of 69 countries on the application of transfer pricing regulations and methods of assessing the transfer pricing file have been analysed. The research results indicate that countries with developed economies and high tax burdens have more rigid transfer pricing tax regulations, the aim of which is to prevent tax evasion through transfer pricing. At the same time, emerging economies with a more lenient tax system do not pay particular attention to transfer pricing, but provide clear regulations on the methods of assessing the transfer pricing case. At the other end of the spectrum there are weakly developed countries, which apply OECD transfer pricing regulations but are flawed in their practical application. The results of the research are of real use both to national and international regulators and to multinationals applying transfer pricing in intra-group transactions.